Life cycle analysis of a building integrated photovoltaic system operating in Bogotá, Colombia (2020)
In this study, the environmental behavior was characterized for a 840 Wp building-integrated photovoltaic (BIPV) system installed in the Department of Physics of the Faculty of Sciences at the National University of Colombia, Bogota campus. The methodology focused on the application of the international technical standards for Life Cycle Analysis (LCA) from cradle to grave based on the NTC ISO 14040 and NTC ISO 1404 standards, which regulate the methodological procedure. This article is based on comparing the potential of environmental impacts of five power generation scenarios, taking as reference the installation of the photovoltaic system (PV) at the University. During the analysis it was possible to determine that energy generation with coal has a greatest environmental impact compared with photovoltaics: 84% and 6% respectively. This represents 1138.8 gCO2eq/kWh for coal, compared to 35 gCO2eq/kWh for the PV system.